2012
DOI: 10.1371/journal.pone.0036234
|View full text |Cite
|
Sign up to set email alerts
|

Digital Gene Expression Analysis Based on Integrated De Novo Transcriptome Assembly of Sweet Potato [Ipomoea batatas (L.) Lam.]

Abstract: BackgroundSweet potato (Ipomoea batatas L. [Lam.]) ranks among the top six most important food crops in the world. It is widely grown throughout the world with high and stable yield, strong adaptability, rich nutrient content, and multiple uses. However, little is known about the molecular biology of this important non-model organism due to lack of genomic resources. Hence, studies based on high-throughput sequencing technologies are needed to get a comprehensive and integrated genomic resource and better unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
163
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(179 citation statements)
references
References 76 publications
11
163
4
1
Order By: Relevance
“…Analysis of annotated transcripts in the sweet potato transcriptome generated and characterized in our previous studies (Tao et al 2012) revealed the presence of AGPase gene family members, including two genes for SSs and four for LSs. Primers specific for the sequences encoding each large and small AGPase subunit were accordingly synthesized and used for full-length cDNA cloning and sequencing.…”
Section: Cloning and Analysis Of Sweet Potato Agpase Subunit Cdnasmentioning
confidence: 95%
See 3 more Smart Citations
“…Analysis of annotated transcripts in the sweet potato transcriptome generated and characterized in our previous studies (Tao et al 2012) revealed the presence of AGPase gene family members, including two genes for SSs and four for LSs. Primers specific for the sequences encoding each large and small AGPase subunit were accordingly synthesized and used for full-length cDNA cloning and sequencing.…”
Section: Cloning and Analysis Of Sweet Potato Agpase Subunit Cdnasmentioning
confidence: 95%
“…In previous studies, we carried out Illumina DGE tag profiling of different sweet potato tissues, including young leaves, mature leaves, stems, fibrous roots, and tuberous roots at two developmental stages (initial and harvestable) (Tao et al 2012). In the present study, we analyzed the expression patterns of six AGPase subunits that were previously uncovered by the DGE tag profiling (Table 2).…”
Section: Expression Of Agpase Subunits In Sweet Potatomentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, studying of transcriptome will provide important insights into the critical transcription factors and regulatory enzymes, their expression patterns, and the regulation of transcribed regions in drought stress conditions. Compared with the former methods, RNA-seq technologies are much simpler and more cost-effective, and wildly used in many plant species (Zhang et al, 2014;Robertson et al, 2010) for discovering novel transcripts and comparing gene expression, for instance, Ipomoea batatas (Tao et al, 2012), Ipomoea nil (Wei et al, 2015), Brassica napus (Trick et al, 2009), Zea mays , and Picrorhiza kurrooa (Gahlan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%